2015
DOI: 10.1111/are.12730
|View full text |Cite
|
Sign up to set email alerts
|

The tolerance threshold of Chinese sucker to total dissolved gas supersaturation

Abstract: Total dissolved gas (TDG) supersaturation generated in the river may result in gas bubble disease to Chinese sucker (Myxocyprinus asiaticus Bleeker) and cause their mortality. To assess the effects of TDG supersaturation on Chinese suckers in laboratory, juvenile fish were exposed to different levels of TDG supersaturated water. All of the fish died when the TDG saturation reached and exceeded 125%, but none died at TDG of 120% saturation in 96 h. To evaluate the effects of intermittent exposure of TDG supersa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 8 publications
2
32
0
Order By: Relevance
“…Many studies have described the signs of GBD in fish, such excessive bubbles on fins, exophthalmia and haemorrhages of the gills and caudal fins (Hans, Mesa, & Maule, ; Huang et al, ; Stroud, Bouck, & Nebeker, ; Westgard, ; Yuan, Wang, Zhou, An, & Li, ). Some abnormal behaviours (e.g., swimming fast, breathing rapidly and moving back and forth) have been observed in previous studies (Cao et al, ; Chen et al, ; Yuan et al, ). Similar results were obtained in this study.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Many studies have described the signs of GBD in fish, such excessive bubbles on fins, exophthalmia and haemorrhages of the gills and caudal fins (Hans, Mesa, & Maule, ; Huang et al, ; Stroud, Bouck, & Nebeker, ; Westgard, ; Yuan, Wang, Zhou, An, & Li, ). Some abnormal behaviours (e.g., swimming fast, breathing rapidly and moving back and forth) have been observed in previous studies (Cao et al, ; Chen et al, ; Yuan et al, ). Similar results were obtained in this study.…”
Section: Discussionmentioning
confidence: 54%
“…Mortality occurs easily in fish subjected to TDG supersaturated water (Beiningen & Ebel, ; Cao et al, ; Elston, ; Katrine, Hilde, & Atle, ). Long exposure times or high TDG supersaturation levels could cause increased mortality (Alderdice & Jensen, ; Bouck, ; Cao et al, ; May, ). In this study, increased TDG supersaturation levels and exposure times reduced the survival time under the same SS concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the LT 50 values of juvenile grass carp decreased significantly with increasing TDG level. Furthermore, related studies have been performed to evaluate the influence of TDG supersaturation on the different species inhabiting the Yangtze River (e.g., Prenant's schizothoracin, Rock carp, Chinese sucker and Silver carp) [14,15,44,45]. Table 3 describes the LT 50 values of four species and juvenile grass carp at four TDG levels (125%, 130%, 135% and 140%).…”
Section: Discussionmentioning
confidence: 99%
“…Limiting the TDG levels to less than 115% is effective in reducing the effect of long-term exposure of juvenile grass carp to TDG. In addition, long recovery time should be considered for formulating schemes during flood discharge [44]. This possibility should attract attention when formulating reservoir operation schemes and planning protective measures for fish inhabiting downstream of dams.…”
Section: Discussionmentioning
confidence: 99%
“…The horizontal avoidance percentage has been used to evaluate the ability of fish to avoid TDG‐supersaturated water in the horizontal direction, with the vertical water depth used to evaluate the ability of fish to use a depth compensation technique to avoid TDG‐supersaturated water. Several studies have examined the tolerance and avoidance characteristics of rare and endemic fish in the TDG‐supersaturated water of the upper Yangtze River over the past 10 years (Huang et al, 2010; Chen et al, 2012; Jiang et al, 2013; Zhang, Du, Wang, & Li, 2014; Wang, Liang, Tuo, Li, & Hodges, 2015; Wang, Li, et al, 2015; Wang, Zhang, Zeng, & Li, 2015; Cao et al, 2016; Xue, Li, et al, 2019; Xue, Wang, Liang, Li, & Li, 2019). However, studies of the tolerance and avoidance characteristics of fish are complicated and require extensive tests.…”
Section: Introductionmentioning
confidence: 99%